If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -19(-4h + -7k + 5) = 0 Reorder the terms: -19(5 + -4h + -7k) = 0 (5 * -19 + -4h * -19 + -7k * -19) = 0 (-95 + 76h + 133k) = 0 Solving -95 + 76h + 133k = 0 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '95' to each side of the equation. -95 + 76h + 95 + 133k = 0 + 95 Reorder the terms: -95 + 95 + 76h + 133k = 0 + 95 Combine like terms: -95 + 95 = 0 0 + 76h + 133k = 0 + 95 76h + 133k = 0 + 95 Combine like terms: 0 + 95 = 95 76h + 133k = 95 Add '-133k' to each side of the equation. 76h + 133k + -133k = 95 + -133k Combine like terms: 133k + -133k = 0 76h + 0 = 95 + -133k 76h = 95 + -133k Divide each side by '76'. h = 1.25 + -1.75k Simplifying h = 1.25 + -1.75k
| 6m-4+6m=-16 | | -3/5=y-1/2 | | (-9*6)+-4= | | 2(6x+130)=5x+164 | | 7(m+7)=40-2m | | 9y+9=15 | | X+x1/2x+1/2x=360 | | (6+2a)=1/2(4a-6) | | 4w-3w+2w+8=-16 | | 5x+6(x+10)=170 | | 15=2a-5a | | n/6=n/2-7/3 | | -4p+4=12 | | 21=-x+4x+9 | | (9*6)+-4= | | 6x-5x=4 | | -9(n-12)=3(1+8n)-12n | | x=40/(x+6) | | y=2x^3-3x^2-36x | | (4/a-2)+(5/a+2)=(5/a^2-4) | | b-5/4=b+2/3 | | -13=3-2x-4 | | -8x(.09)x(-.5)= | | -110=-5x | | 6r-7(4r+2)=28-8r | | 10+5x-7=8x+8-3x | | 3x^3y+3x^2-9x^2y=0 | | 4.50+0.05x=0.2x | | 8n+2=-2n-8 | | p-38=47/5(h-7) | | -(2x-7)=7-2x | | 1-6n-1=18 |